Pelatihan dan Pendampingan Peningkatan Kesiapan Karyawan dalam Menghadapi Digitalisasi di UMKM Desa Sinarbaya Karawang - Apriani, Zenita; Pertiwi, Wike; Hidayaty, Dwi Epty; Triadinda, Dexi (Irajagaddhita, 2025)
This community service activity aims to strengthen the readiness of micro, small, and medium enterprises (MSMEs) in facing the digitalization era through employee training and mentoring. The program was implemented at Nasi Kuning MSME in Sinarbaya Village, Karawang. The main problems faced include limited manpower, lack of knowledge in production management, and minimal digital marketing capabilities. The methods used include observation, interviews, workshops, and direct mentoring sessions. The results showed that the MSME owner and employee had improved their understanding of social media use, created a digital identity for their business through Google Maps and Instagram, and developed skills in calculating production costs. The program succeeded in enhancing the MSME’s digital literacy, managerial capacity, and promotional independence. Follow-up programs are recommended to maintain sustainability and deepen the use of digital tools for business development.